PENGARUH LATIHAN SIDE-TO-SIDE SHUFFLE JUMP TERHADAP PENINGKATAN DAYA LEDAK OTOT TUNGKAI MAHASISWA PENJASKESREK UNIVERSITAS BUNG HATTA - Meirony, Arfon (Gelanggang Pendidikan Jasmani Indonesia, 2018)
The times, a coach is required to be able to design simple exercises, Explosive power is in many sports and daily life, One of the many exercises that can increase leg muscle explosive power is an exercise Side-to-Side Shuffle Jump. This is research experiment. The technique of determine method his area purposive sampling of sample, 17 samples were given an early test vertical jump (modified sargent jump) and continued with the treatment of 14 sessions, next the pree test to see effect of the exercise. Test used is t-test, see the effect of mean significant Î± 0,05. The results of the posttest mean of 98.26, preetest mean of 100.45. The result of ttest (6.22)>ttable (2.11). With hypothesis research is accepted